Reform of Islamic Inheritance Law: The Influence of Customary Law on the Institution of Wasiat Wajibah in Islamic Law - Fatahullah; Adi Sulistiyono; Burhanudin Harahap (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
This research aims to investigate the status of the deceased's close relatives, including adopted children, illegitimate children, and children of diverse religions, within the family structure and their legitimate legal standing, thereby establishing their entitlement to inherit the decedent's property. Nonetheless, the viewpoint of the inheritance legal framework in Indonesia about the status of these immediate relatives is markedly distinct. The employed methodology is a normative or doctrinal legal study utilizing a legislative approach and analysis. Wasiat wajibah is an institution in Islamic law in Indonesia to address the problem of differing paradigms between customary law, which recognises all positions and rights of adopted children, and Islamic law, which "only" recognises adoption but does not allow mutual inheritance. The underlying thought of wasiat wajibah in Islamic jurisprudence is intended to provide a sense of justice to adopted children or those close to the heir, but they are religiously barred from inheriting a share of the inheritance. Finally, the mandatory will through Article 209 of the Compilation of Islamic Law (KHI) has filled the ambiguity in Islamic law by granting 1/3 of the inheritance to the adopted child from the property left by the adoptive parents. It is necessary to set standards for the future implementation of mandatory wills to ensure that judges' interpretations of these documents do not negatively impact the interests of the principal heirs.